The Influence Of Work Motivation On Employee Performance At Paradigma Restaurant And Café, Cikini - Gita Putri, Octaviani (Universitas Terbuka, 2025)
This study aims to examine the influence of work motivation on employee performance at Paradigma Restaurant and Cafe, Cikini. The sample consisted of all Paradigma employees, totaling 32 individuals. Primary data was collected through observations and questionnaires, while secondary data was also utilized. The analytical method employed was a descriptive method with a quantitative approach, incorporating validity tests, reliability tests, descriptive statistics, the coefficient of determination test, correlation tests, and simple linear regression analysis. The findings indicate that the average score for the work motivation variable (X) was 3.14, placing it in the